The Development of Film-Based Literary Materials which Support Character Education - Nugrahani, Farida (LPMPP Universitas Negeri Yogyakarta, 2017)
Abstract:This study aims to develop literary materials based on film, to test the teaching materials, and to describe the values of characters embedded in it. This research development follows the Plomp (1997) model, with four stages, including initial assessment, design, realization (construction), validation and revision. The developed prototype of the teaching materials was tested in high schools. The resultsreveal that (1) literary materials based on film can be compiled in the form of learning tools, including student books and teacher books according to Curriculum 2013; (2) the literary materials developed are valid, practical, and effective for use to improve student’s motivation and learning outcomes; (3) the character values contained in the instructional materials are trustworthiness, caring, and citizenship. Keywords: literary materials, film, practical, effective, character education. PENGEMBANGAN BAHAN AJAR SASTRA BERBASIS FILM YANG MENDUKUNG PENDIDIKAN KARAKTER Abstrak:Penelitian ini bertujuan untuk mengembangkan bahan ajar sastra berbasis media film, hasil uji bahan ajar, dan mendeskripsikan nilai-nilai karakter yang terdapat di dalamnya. Penelitian pengembangan ini mengikuti model Plomp (1997) dengan empat tahap, meliputi pengkajian awal, perancangan, realisasi (konstruksi), validasi dan revisi. Prototipe bahan ajar yang dikembangkan diujicobakan di SMA.Hasil penelitian menunjukkan bahwa (1) bahan ajar sastra berbasis media film dapat disusun dalam bentuk perangkat pembelajaran meliputi buku siswa dan buku guru sesuai Kurikulum 2013; (2) bahan ajar sastra yang disusun bersifat valid, praktis, dan efektif untuk digunakan dalam meningkatkan motivasi dan hasil belajar sastra siswa SMA; (3) nilai-nilai karakter yang terdapat di dalam bahan ajar yang dikembangkan adalah rasa percaya diri (trustworthiness), kepedulian (caring), dan kebangsaan (citizenship). Kata kunci: bahan ajar sastra, film, praktis, efektif, pendidikan karakter.